Poetic of the Excision: Looking Out, Staring - Sousa Pardo, Carmen (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
This article aims to study how the gesture of looking out has been sensitized in the plastic arts since Romanticism, specifically in its representation in windows or balconies during the historical avant-gardes. Considering windows as frames of the excision and using the term coined by Argullol, the awareness of this gesture is seen as the will to transgress their own human or social space assigned. That is, the attempt to overcome the inescapable excision that the window imposes on the individual will actually be the attempt to put an end the profound solipsism that lies in contemporary individuals.